Look at the future -perceptions of fertility counseling and decision-making among adolescents and their parents in the context of hematopoietic stem cell transplantation—experience of one major center for pediatric stem cell transplantation - Barnbrock, Anke; Hamannt, Fabienne; Salzmann-Manrique, Emilia; Rohm, Theresa; Lange, Sandra; Bader, Peter; Jarisch, Andrea (Frontiers in Pediatrics, 2023)
Increasing survival rates after hematopoietic stem cell transplantation (HSCT) in childhood should put focus on improving the quality of life as adults. An essential aspect is fertility and its preservation. In order to take advantage of the possibility of fertility preservation, fertility counseling should be provided to patients and their parents prior to gonadotoxic therapies.The aim of this survey was to analyze the impact of fertility counseling in pediatric stem cell transplantation in patients and their parents using questionnaires designed for the study questions. 51 parents and 7 adolescent patients were interviewed between February 2019 to October 2021 about the counseling, their perceptions of fertility issues, and the nature of decision-making concerning fertility preservation. The study included patients with malignant (e.g., leukemia, lymphoma, neuroblastoma) and nonmalignant diseases (e.g., thalassemia, sickle cell disease, immunodeficiency) who received counseling on fertility preservation before HSCT based on an in-house standard and analysed the impact for both groups.Two-thirds of the study participants were concerned about having children and grandchildren respectively; for half of all respondents, the topic of fertility and fertility preservation proved to be hopeful. 40% of the study participants were burdened by the risk of possible fertility limitations after HSCT. Concerns about fertility was particularly significant for parents whose children were advised to undergo fertility preservation. Parents of children < 12 years found deciding on appropriate measures more difficult. Parents with children > 7 years involved their children in the decision.All study participants agreed that fertility counseling had not negatively affected the parent-child relationship. More than 90% of all study participants were in favor of addressing fertility, its potential limitations and fertility preservation measures before HSCT. There was no significant difference between the malignant and the nonmalignant cohort in all study questions.Overall, the standardized fertility counseling provided in our center of pediatric stem cell transplantation resulted in high satisfaction among patients and their parents. Multiple counseling on infertility risk, including the younger patients in the decisionmaking and further options after gonadotoxic therapy may increase the satisfaction of the counseled patients and their parents.